Investigation of Mean Platelet Volume and Platelet Count in the Blood of Patients with Migraine - Sefer Varol; Eşref Akıl; Mehmet Uğur Çevik; Tahsin Çelepkolu; Yavuz Yücel; Mehmet Halis Tanrıverdi; Mehmet Ufuk Aluçlu; Ertuğrul Uzar (Türk Nöroloji Dergisi, 2013)
OBJECTIVE: Mean platelet volume (MVP) is an indicator for platelet function and activation. Studies researching MPV and platelet level on the patients with migraine are less. Our aim with this study is to search whether MPV and platelet count which are indicators for platelet activation in individuals with migraine when compared with healthy controls in a wide case series. METHODS: 193 patients (female/male: 128/65, average age: 31, 66±9.01) who have referred to Neurology Polyclinic of Dicle University, faculty of medicine between January 2010 and January 2012 and have been diagnosed with Migraine according to 2004 diagnosis criteria of International Headache Society (IHS) and 119 healthy individuals (female/male: 73/46, averge age: 32.27±9.88) who have referred to Family Practice Polyclinic and Blood Bank were involved into the study. MPV and platelet counts between the patients diagnosed with migraine and healthy control group who are similar for age and gender were compared. RESULTS: A statistically insignificant increase was found in MPV in patients with migraine (7.98±1.34 fL) when compared with the control group (7.85 ± 0.96 fL) (p=0.34). Platelet level was significantly lower in patients with migraine (367,6 ± 74.2) than the control group (286.9±68.3) (p=0.02). CONCLUSION: While we have found lower platelet levels in the patients with migraine than the healthy control group, we have found statistically insignificant increase in MPV in patients with migraine than the control group. These findings may indicate an insignificant platelet activation in patients with migraine.New prospective studies are necessary on this subject